Spiritual Jewish Criminology: The Basic Premises and the Pyramid - Ben Yair, Yitzhak (International journal of offender therapy and comparative criminology, 2021)
Religion and spiritual traditions entail vast wisdom and knowledge which have proved their productivity in achieving criminal rehabilitation, crime desistance, and crime prevention. Unfortunately, the literature on their role is relatively scarce and was not, until recently, regarded as part of mainstream criminology. This study used a hermeneutic phenomenological approach in which 39 participants were interviewed and many of the religious scriptures selected at their recommendation were analyzed. The findings reveal three central and unique themes that deal with the purpose of creation, human nature, and the question of free will. Through these premises, this study suggests that Spiritual Jewish criminology, a faith-based theory stemming from Jewish scriptures, offers a universal paradigm that explains a person’s life as a spiritual journey, completed according to the Pyramid Model. The pyramid is built on two axes that describe a person’s desirable movement: the first ranges from egocentrism to altrocentrism, while the second ranges from materialism to the spiritual. The study’s discussion deals with the Pyramid Model’s ability to explain the causes of delinquency, the onset of a criminal career, and the way out of this criminal world through treatment and rehabilitation.